Gender wage discrimination - Boris Hirsch (IZA World of Labor, 2016)
There are pronounced and persistent wage differences between men and women in all parts of the world. A significant element of these wage disparities can be attributed to differences in worker and workplace characteristics, which are likely to mirror differences in worker productivity. However, a large part of these differences remains unexplained, and it is common to attribute them to discrimination by the employer that is rooted in prejudice against female workers. Yet recent empirical evidence suggests that, to a large extent, the gaps reflect “monopsonistic” wage discrimination—that is, employers exploiting their wage-setting power over women—rather than any sort of prejudice.
Keywords: J42; J71; J16; J31; 330; gender wage gap; wage discrimination; imperfect labor market competition; monopsony power; monopsonistic discrimination